Measurement of CKM matrix elements in single top quark t-channel production in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2020)
The first direct, model-independent measurement is presented of the modulus of the Cabibbo-Kobayashi-Maskawa (CKM) matrix elements vertical bar V-tb vertical bar, vertical bar V-td vertical bar, and vertical bar V-ts vertical bar, in final states enriched in single top quark t-channel events. The analysis uses proton-proton collision data from the LHC, collected during 2016 by the CMS experiment, at a centre-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb(-1). Processes directly sensitive to these matrix elements are considered at both the production and decay vertices of the top quark. In the standard model hypothesis of CKM unitarity, a lower limit of vertical bar V-tb vertical bar > 0.970 is measured at the 95% confidence level. Several theories beyond the standard model are considered, and by releasing all constraints among the involved parameters, the values vertical bar V-tb vertical bar = 0.988 +/- 0.024, and vertical bar V-td vertical bar(2) + vertical bar V-ts vertical bar(2) = 0.06 +/- 0.06, where the uncertainties include both statistical and systematic components, are measured. (C) 2020 The Author. Published by Elsevier B.V.